The association between school bullying involvement and Internet addiction among Chinese Southeastern adolescents: a moderated mediation model with depression and smoking - She, Yuhang; Li, Liping (Frontiers in Psychiatry, 2025)
BackgroundSchool bullying and Internet addiction are both common public health problems for adolescents. Several studies found an association between school bullying and Internet addiction; however, the underlying mediating and moderating mechanisms of the complex relationship between school bullying and Internet addiction are limited.ObjectiveThis study explored the mediating role of depression in the relationship between school bullying and Internet addiction and whether smoking moderated the relationship between school bullying and depression in Chinese southeastern adolescents.MethodsA cross-sectional study was conducted in Guangdong Province in Southeast China in June 2021. Associations between Internet addiction, school bullying, and depression were estimated using Spearman correlation analysis, the mediation effect and moderation effect were examined using Model 4 and Model 7 in the Hayes’ PROCESS macro.ResultsThe results included 1992 adolescents, 23.5% and 28.0% of participants reported experiences of school bullying and Internet addiction, respectively. There was a significant correlation between school bullying, depression, and Internet addiction (p < 0.01). School bullying direct effects on Internet addiction [β = 0.565, SE= 0.053, 95% CI (0.461, 0.669)], depression partially mediated the association between school bullying and Internet addiction, with the mediation effect size being 36.5%. And smoking played a moderating role between school bullying and depression [β = -0.166, SE= 0.058, 95% CI (-0.280, -0.052)].ConclusionsIn Chinese southeastern adolescents, depression mediated the relationship between school bullying and Internet addiction, and smoking moderated the relationship between school bullying and depression.